Formation of mineral phases in self-propagating high-temperature synthesis (SHS) of porous TiNi alloy. (6th February 2019) - Yasenchuk, Yuriy; Gunther, Victor; Marchenko, Ekaterina; Chekalkin, Timofey; Baigonakova, Gulsharat; Hodorenko, Valentina; Gunther, Sergey; Kang, Ji-hoon; Weiss, Sabine; Obrosov, Aleksei
Abstract: The complex structural-phase composition, morphology and elemental composition of surface and nonmetallics in porous TiNi compounds produced by self-propagating high-temperature synthesis (SHS) in a flow reactor in the layer-by-layer combustion mode were analyzed. The samples were investigated using light microscopy (LM), x-ray diffraction (XRD), scanning electron microscopy (SEM), scanning transmission electron microscopy (STEM), and energy dispersive x-ray spectroscopy (EDS). The findings indicate that in addition to the TiNi and Ti2 Ni intermetallic constituents, the pore's surface contains numerous Ti4 Ni2 (O, N, C) nanocrystalline oxycarbonitrides, spinels, polysilicates, and residual amorphous phases. The elemental composition of the surface and crystalline inclusions is investigated by the EDS method. LM, SEM, TEM, and EDS instrumental examination revealed the entire surface comprising a continuous shell of intermetallic superficial bulb-shaped structures, as well as crystalline inclusions of polysilicates and spinels in the intergranular peritectic phase. Prominent morphology was confirmed to appear throughout the pore's surface owing to the interaction of the peritectic liquid (PL) with reaction gases. The epitaxial, nanocrystalline strata of intermetallic oxycarbonitrides were shown to have the intricate nature. Reaction gases chemisorbed by the PL are responsible for the continuous and dense substrate, which ultrafine structure modulates a high corrosion resistance. On the contrary, the sparse and foamy overlay resulted from a convective transfer of the PL by reaction gases facilitates in vivo bio-integration of the alloy. Overall, this sheds light on and may be more indicative of the complex role of superficial strata and nonmetallic crystals in enhanced biocompatibility of the unwrought porous TiNi alloy.